Rapid simultaneous detection of blaoxa-23, Ade-B, int-1, and ISCR-1 in multidrug-resistant Acinetobacter baumannii using single-tube multiplex PCR and high resolution melting assay - Sun H; Xiao G; Zhang J; Pan Z; Chen Y; Xiong F (Infection and Drug Resistance, 2019)
Hengbiao Sun,1,* Gang Xiao,1,* Jing Zhang,1 Zuhan Pan,1 Youming Chen,1 Fu Xiong,21Department of Clinical Laboratory, The Third Affiliated Hospital of Southern Medical University, Guangzhou 510630, People’s Republic of China; 2Department of Medical Genetics, School of Basic Medical Sciences, Southern Medical University, Guangzhou 510515, People’s Republic of China*These authors contributed equally to this work Objective: The aim of this study was to develop a multiplex PCR system for the rapid and simultaneous detection of blaoxa-23, Ade-B, int-1, and ISCR-1 genes in multidrug-resistant Acinetobacter baumannii (MDRAB) using high resolution melting (HRM) assay.Methods: Four pairs of primers were designed, and PCR amplification products were sequenced and compared with NCBI GeneBank sequences to ensure primer specificity. Multiplex PCR was performed using a dedicated HRM reagent, and melting curves and temperatures were able to distinguish the four genes. This method was subsequently used to detect these genes in 79 MDRAB isolates from the Third Affiliated Hospital of Southern Medical University in southern China.Results: Using the HRM assay, 73 out of 79 isolates were found to carry both blaoxa-23 and Ade-B, one isolate carried int-1, two isolates carried both int-1 and ISCR-1, and three isolates carried Ade-B, int-1, and ISCR-1. No isolates carried all four genes. Conclusion: Compared with traditional resistance gene detection methods–PCR and agarose gel electrophoresis-based resistance gene detection methods–the multiplex PCR and HRM assay method was simple, rapid, highly efficient, and cost-effective. Our results showed that blaoxa-23 and Ade-B were the main resistance genotypes in MDRAB.Keywords: blaoxa-23, Ade-B, int-1, ISCR-1, multiplex PCR, high resolution melting